Standardized measurements, landmarks, and meristic counts for cypriniform fishes - Armbruster, Jonathan W. (Zootaxa, 2012)
Standardized measurements and landmarks for traditional morphometrics, landmark-based (partial truss) measurements, and geometric morphometrics for Cypriniformes are described. Standardized meristic counts also are described.